Level Of Reading Anxiety In Arabic Language Among University Students/ مستوى قلق القراءة في اللغة العربية لدى الطلاب الجامعة - Binti Zahar, Nur Adnin; Bin Baharuddin, Harun; Bin Wan Daud, Wan Abdul Aziz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aimed to determine the level of reading anxiety in Arabic among university students in the East Coast region of Malaysia. The study used a quantitative approach through a cross-sectional survey design, with a sample of 132 students from Sultan Zainal Abidin University and Universiti Malaysia Kelantan. Data was collected using the Foreign Language Reading Anxiety Scale (FLRAS) questionnaire adapted from Mikami's study (2019). The results showed that the students' reading anxiety level was generally moderate, with three main anxiety dimensions emerging: unfamiliar texts (high level), linguistic distance (high level), and confidence/enjoyment in reading (high level). The study revealed that unfamiliar vocabulary and grammar constitute the most significant source of anxiety, followed by difficulties related to linguistic and cultural distance between the mother tongue and the Arabic language, in addition to the impact of low self-confidence and fear of making mistakes. The study recommends adopting effective teaching strategies to enhance basic language skills, bridging the cultural gap, building confidence and enhancing motivation through a supportive learning environment, and using technology and multimedia to make Arabic reading more enjoyable and interesting.